2018
DOI: 10.1038/s41598-018-20208-4
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi surface protein Lmp1 facilitates pathogen dissemination through ticks as studied by an artificial membrane feeding system

Abstract: In its natural infection cycle, the pathogen of Lyme borreliosis transits between a tick vector and a mammalian host. As relatively a minor fraction of spirochetes transits between the host and the vector precluding their reliable detection at early infection, artificial membrane feeders emerged as useful tools to study roles of spirochete proteins in pathogen entry, persistence, and exit through ticks. Here we report the development of a modified membrane feeder to study the role of a Borrelia burgdorferi sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Such membrane feeding systems have been useful for introducing specific pathogens into I. scapularis and to test different acaricides effectiveness on I. ricinus (Krober and Guerin, 2007;Oliver et al, 2016). Several recent studies have used these systems to elucidate the contribution of B. burgdorferi proteins in acquisition and transmission of mutant strains and to assess nutritional requirements for tick reproduction (Perner et al, 2016;Bernard et al, 2018;Hart et al, 2018;Koci et al, 2018). Larval ticks, though, did not successfully feed with this technique, likely due to the inability of the smaller mouthparts of larvae to penetrate through the thickness of the silicone membrane (Oliver et al, 2016).…”
Section: New Dimensions For the Study Of Tick Biologymentioning
confidence: 99%
“…Such membrane feeding systems have been useful for introducing specific pathogens into I. scapularis and to test different acaricides effectiveness on I. ricinus (Krober and Guerin, 2007;Oliver et al, 2016). Several recent studies have used these systems to elucidate the contribution of B. burgdorferi proteins in acquisition and transmission of mutant strains and to assess nutritional requirements for tick reproduction (Perner et al, 2016;Bernard et al, 2018;Hart et al, 2018;Koci et al, 2018). Larval ticks, though, did not successfully feed with this technique, likely due to the inability of the smaller mouthparts of larvae to penetrate through the thickness of the silicone membrane (Oliver et al, 2016).…”
Section: New Dimensions For the Study Of Tick Biologymentioning
confidence: 99%
“…Some molecules that have been shown to have a function within the tick vector include the Outer surface protein A (OspA) which binds to the vector midgut molecule TROSPA (Pal et al, 2004); BBE31 which binds to the vector molecule Tre31, a protein secreted by tick midgut epithelial cells (Zhang et al, 2011); PdeB, a phosphodiesterase required for survival in, and transmission by, ticks; Lpm1, a surface molecule, depletion of which inhibits Borrelia in the vector (Koci et al, 2018); BB0365, BB0690, BptA, lp6.6, BBk32 are all required for persistence in the tick, while antigen P35 (BBA64) may play a role in tick-tohost transmission (Fikrig et al, 2000;Radolf et al, 2012;Brandt et al, 2014). In a recent study using transposon-based gene interruption approach, >100 genes were shown to be involved in Borrelia survival in larval ticks (Phelan et al, 2019).…”
Section: Borrelia Genesmentioning
confidence: 99%
“…Several membrane-translocated proteins are important for Bb transmission and persistence. In ticks, OspA is essential for colonization and survival 9 and Lmp1 facilitates dissemination 10 . BB0405 is necessary for transmission from tick to mouse and for establishing infection in mice 11 .…”
Section: Introductionmentioning
confidence: 99%